Blood pressure changes during the the COVID-19 pandemic and associated lockdown period. (14th October 2021) - Girerd, N; Meune, C; Duarte, K; Vercamer, V; Lopez-Sublet, M; Mourad, J J
Abstract: Background: Despite widespread investigation into the incidence of acute myocardial infarction during the COVID-19 pandemic and associated lockdown, no study has examined the situation's impact on blood pressure (BP) levels. Methods: Measurements of BP and heart rate (HR) were obtained from persons living in the Paris urban area using connected home BP monitors (accessible to patients and health providers through a secured server). Three time periods of e-Health recordings were compared: during the pandemic prior to the lockdown, during the lockdown and the same time period in 2019. Results: A total of 297, 089 BP recordings from 2, 273 participants (age 56.3±12.8 years, 81.1% male) were made. During confinement, systolic BP gradually decreased by 3 mmHg (−2.4 to −3.9), and diastolic BP, by 1.5 mmHg (−1.4 to −2.2) (all p<0.001); this decrease was greater for participants with higher BP (p<0.0001 each). No significant variation in HR was noted. Conclusion: Among a very large cohort, we observed a significant decrease in home BP measured with e-Health devices during the first lockdown period. This study emphasizes the research potential of e-Health during the Covid crisis. Funding Acknowledgement: Type of funding sources: None.